Does Knowing Someone with Breast Cancer Influence the Prevalence of Adherence to Breast and Cervical Cancer Screening? - Igor Vilela Brum; Tamara Cristina Gomes Ferraz Rodrigues; Estela Gelain Junges Laporte; Fernando Monteiro Aarestrup; Geraldo Sergio Farinazzo Vitral; Bruno Eduardo Pereira Laporte (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To evaluate the prevalence of adherence to screening methods for breast and cervical cancer in patients attended at a university hospital and to investigate whether knowing someone with breast cancer, moreover belonging to the patient's family, affects the adherence to the screening recommendations. Methods This was a cross-sectional and quantitative study. A structured interview was applied to a sample of 820 women, between 20 and 69 years old, who attended a university hospital in the city of Juiz de for a, MG, Brazil. For the analysis, the chi-square test was used to assess possible associations between the variables, and the significance level was set at p-value ≤ 0.05 for a confidence interval (CI) of 95%. Results More than 95.0% of the sample performed mammography and cervical cytology exam; 62.9% reported knowing someone who has or had breast cancer, and this group was more likely to perform breast self-examination (64.9%; odds ratio [OR] 1.5; 95% CI 1.12-2.00), clinical breast examination (91.5%; OR 2.11; 95% CI 1.37-3.36), breast ultrasound (32.9%; OR 1.81, 95% CI 1.30-2.51), and to have had an appointment with a breast specialist (28.5%; OR 1.98, 95% CI 1.38-2.82).Women with family history of breast cancer showed higher propensity to perform breast self-examination (71.0%; OR 1.53 95% CI 1.04-2.26). Conclusion There was high adherence to the recommended screening practices; knowing someone with breast cancer might make women more sensitive to this issue as they were more likely to undergo methods which are not recommended for the screening of the general population, such as breast ultrasound and specialist consultation; family history is possibly an additional cause of concern.